STRATEGI PENGEMBANGAN PANTAI SAWANGAN SEBAGAI DAYA TARIK WISATA NUSA DUA - Nainggolan, Deby Marlina; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 3 No 2 (2015): VOL 3, NO 2 (2015): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2015.v03.i02.p08, 2015)
ABSTRACT This study aims to identify and understand the potential of Sawangan Beach and strategize development Sawangan Beach as a tourist attraction. Data obtained in the form of responses and descriptions of the communit y , community leaders and traditiona l Peminge village opinion rating. The data obtained through observation, interviews literature. Data were analyzed by using SWOT analysis. Based on the SWOT analysis approach, there are some basic problems in Sawangan Beach are a lack of community involvement in the development of plunging into a tourist attraction, the lack of promotion by the local government, the lack of tourism facilities and less organized Sawangan Beach coast guar d . The strategy is to be done in developing Sawangan Beach as a tourist attraction is to empower the community about the development of tourism on the Sawangan Beach , providing information and communication facilities for tourists, building facilities to support the government's tourism, tourism promotion in various media, involving the government in the development of Sawangan Beach as a tourist attraction. The suggestion of the researcher is that should a major player in the construction and development of tourist attraction is the Sawangan Beach local communities and governments, and provides facilities that support the development of Sawangan Beac h , such as the coast guard, holding the promotion of tourist attraction Sawangan Beach .
Keywords: Strategy of development, tourist attraction, Sawangan Beach, Nusa Dua